Eco-Friendly Green Synthesis of Silver Nanoparticles Using Natural Mineral Resin Shilajit: Characterization and Evaluation of their Antifungal, Antibacterial, and Anticancer Activities - Cintesun, Sener; Karpuz, Mehmet Mensur; Seyhan, Mehmet Fatih; Marakli, Sevgi (SPRINGERNATURE, 2025)
Shilajit, also known as mumie or mumijo, is a natural resin that forms by the slow decomposition and compaction of plant material and other organic matter over centuries in rock cracks and cavities found in the high mountains. In this study, silver nanoparticles (AgNPs) were synthesized via green synthesis using shilajit. During the synthesis, a range of silver nitrate concentrations and varying temperature parameters were tested to determine the optimum conditions for the reaction. The synthesized AgNPs were characterized by various techniques, including ultraviolet-visible (UV) spectrophotometry, dynamic light scattering (DLS)-Zeta Sizer, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and field emission scanning electron microscopy (FESEM). Furthermore, the total phenolic content and free radical scavenging activity were investigated. The antibacterial effect of AgNPs was investigated on Escherichia coli and Staphylococcus aureus bacteria, while the antifungal activity of AgNPs was evaluated on two Fusarium strains. The anticancer activity of AgNPs was investigated on MCF-7 breast cancer cell lines. AgNPs were spherical, with an average particle size of 222.9 +/- 7.53 nm. The phenolic content of shilajit extract was measured at 41.94 +/- 2.59 (mg GAE/g), while the phenolic content of AgNPs was 51.69 +/- 5.93 (mg GAE/g). However, the shilajit extract demonstrated superior DPPH scavenging activity compared to the AgNPs. The findings of the present study demonstrate that AgNPs exhibit a more pronounced inhibitory effect on E. coli, along with a suppressive effect ranging from 50 to 90% on the two tested Fusarium strains. Moreover, AgNPs demonstrate a comparable and substantial cytotoxic effect against MCF-7 cells at 24 (IC50: 11.50 mu g/mL) and 48 (IC50: 16.26 mu g/mL) h. These findings demonstrate that AgNPs, obtained through green synthesis using shilajit, possess a wide range of biological activities and have the potential to be considered as a therapeutic agent in future studies. [GRAPHICS] .
Keywords: Shilajit; Silver nanoparticles; Green synthesis; Antimicrobial; Anticancer; LEAF EXTRACT; ANTIOXIDANT; Chemistry